2017
DOI: 10.1002/ppul.23716
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa and post-tracheotomy bacterial respiratory tract infection readmissions

Abstract: Objective Identify risk factors for readmission due to a bacterial tracheostomy-associated respiratory tract infection (bTARTI) within 12 months of discharge after tracheotomy. Design/Methods We performed a retrospective cohort study of 240 children who underwent tracheotomy and were discharged with tracheotsomy in place between 1/1/2005 and 6/30/2013. Children with prolonged total or post-tracheotomy length of stay (LOS), less than 12 months of follow-up, or who died during the index hospitalization were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 32 publications
5
54
1
4
Order By: Relevance
“…Some factors were associated with decreased risk for readmission for a bRTI, including congenital heart surgery repair during the index hospitalization, trauma comorbidity, and chronic ventilator dependence. The observed median time for bRTI hospital readmission in the current study was longer than a previous, single‐center study of post‐tracheotomy bRTI readmission …”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Some factors were associated with decreased risk for readmission for a bRTI, including congenital heart surgery repair during the index hospitalization, trauma comorbidity, and chronic ventilator dependence. The observed median time for bRTI hospital readmission in the current study was longer than a previous, single‐center study of post‐tracheotomy bRTI readmission …”
Section: Discussioncontrasting
confidence: 73%
“…Cox proportional hazard model of factors associated with hospitalizations for a bacterial respiratory tract infection after tracheotomy Increased risk of hospital readmission for a bRTI and poorer outcomes in children with younger age, Hispanic ethnicity and government payer status complements findings of previous studies8,12,14,15,[22][23][24] and highlight potential opportunities to optimize…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The authors of recent work have demonstrated that P aeruginosa is a common respiratory isolate in pediatric patients admitted with aspiration pneumonia 25,26 and in pediatric patients after tracheotomy. 27,28 This result complements recent work revealing an association between P aeruginosa isolation and poorer outcomes, including readmission for a bTARTI, 28 ICU admission, and intubation. 26 Receiving antibiotics targeting P aeruginosa may be a proxy for higher illness severity or increased likelihood of having multidrug-resistant organisms.…”
Section: Principal Diagnosissupporting
confidence: 82%
“…Recent studies examining populations of children with cerebral palsy and/or tracheostomy have emphasized the high rates of carriage and infection rates with Gram-negative and drug-resistant bacteria; in particular, P. aeruginosa accounts for 50%-72% of pathogenic bacteria. 11,12,38,40 These studies note the generally poor outcomes of children with P. aeruginosa-including multiple and longer hospitalizations, frequent readmissions, and the increased severity of pneumonia, including the need for ICU admission, pleural effusions, the need for intubation, and mortality. 11,12,38,40,41 In our study, nearly 35% of children who received anaerobic, Gram-negative, and P. aeruginosa coverage experienced acute respiratory failure during hospitalization compared with 20% of children who received other therapies.…”
Section: Discussionmentioning
confidence: 99%